A portable ultrahigh‐vacuum system for advanced synchrotron radiation studies of thin films and nanostructures: EuSi2 nano‐islands. (1st January 2015) - Ibrahimkutty, Shyjumon; Seiler, Anja; Prüßmann, Tim; Vitova, Tonya; Pradip, Ramu; Bauder, Olga; Wochner, Peter; Plech, Anton; Baumbach, Tilo; Stankov, Svetoslav
<x xml:space="preserve">Abstract</x> A portable ultrahigh‐vacuum system optimized for in situ variable‐temperature X‐ray scattering and spectroscopy experiments at synchrotron radiation beamlines was constructed and brought into operation at the synchrotron radiation facility ANKA of the Karlsruhe Institute of Technology, Germany. Here the main features of the new instrument are described and its capabilities demonstrated. The surface morphology, structure and stoichiometry of EuSi2 nano‐islands are determined by in situ grazing‐incidence small‐angle X‐ray scattering and X‐ray absorption spectroscopy. A size reduction of about a factor of two of the nano‐islands due to silicide decomposition and Eu desorption is observed after sample annealing at 1270 K for 30 min.